2022
DOI: 10.21037/qims-22-32
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion magnetic resonance imaging in the differentiation between glioma recurrence and pseudoprogression: a systematic review, meta-analysis and meta-regression

Abstract: Background: Tumor recurrence and pseudoprogression (PsP) have similar imaging manifestations in conventional magnetic resonance imaging (MRI), although the subsequent treatments are completely different. This study aimed to evaluate the value of perfusion-weighted imaging (PWI) in differentiating PsP from glioma recurrence.Methods: A comprehensive literature search was performed to evaluate clinical studies focused on differentiating recurrent glioma from PsP using PWI, including dynamic susceptibility contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
(78 reference statements)
3
15
0
Order By: Relevance
“…35 In prior meta-analyses, DSC-PWI has been suggested to exhibit greater diagnostic utility when differentiating between PsP and RT in HGG patients relative to individuals with low-grade glioma. 1,2 Cerebral blood volume and CBF are the primary DSC-PWI indices, and the present results suggest that the diagnostic performance of these indices is comparable when distinguishing between PsP and RT while analyzing patients with HGG. Importantly, the high AUC values for both CBV and CBF suggest that both are associated with a high degree of diagnostic accuracy.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…35 In prior meta-analyses, DSC-PWI has been suggested to exhibit greater diagnostic utility when differentiating between PsP and RT in HGG patients relative to individuals with low-grade glioma. 1,2 Cerebral blood volume and CBF are the primary DSC-PWI indices, and the present results suggest that the diagnostic performance of these indices is comparable when distinguishing between PsP and RT while analyzing patients with HGG. Importantly, the high AUC values for both CBV and CBF suggest that both are associated with a high degree of diagnostic accuracy.…”
Section: Discussionsupporting
confidence: 50%
“…Notably, subgroup and meta-regression analysis results suggested that study design, blinding situation, MRI field strength, and CBV type did not affect diagnostic accuracy, in line with prior meta-analyses. 1,2 Contrast-enhanced PWI strategies primarily consist of DSC-PWI and dynamic contrast-enhanced MRI. 1,3,37 Dynamic contrast-enhanced MRI exhibits a higher level of spatial resolution than that afforded by DSC-PWI, offering more insight regarding tumor perfusion while better reflecting vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several larger, population-based studies that support MR perfusion imaging as a basic diagnostic tool for identifying suspect lesions. Regarding DCE-MRI, Zhang et al in their meta-analysis of 40 studies including 876 cases showed a pooled sensitivity and specificity of 0.83 each in differentiation between tumor recurrence and pseudo progression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%